Mass Media and Music Consumption in High School Students from Brazil - de Quadros Júnior, João Fortunato Soares (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The main objective of this article is to discuss the influence of mass media and some other non-formal education agents in the musical preferences of high school students in Brazil. The research was developed with 940 students (men and women) from Vitória (Es- pirito Santo – Brazil). They confirmed mass media to be the key agent determining their musical preferences, being the internet and the radio the most relevant, followed by T.V and peer influence. This fact emphasizes the importance of creating new public policies that favor the access and dissemination of music through different media, giving a special value to its insertion in formal and non-formal education. The importance of this strategy lies in the fact that it would probably help moderate the potential dominance of media agents over educational figures and institutions